Realization - Symphony in the Flint Hills, Inc. (Symphony in the Flint Hills, 2019)
Introduction: "Now we have electric lights and the stars are hard to see. At sea we hide in luxurious cabins and do not even question the machinery which holds us steadily on our course." -- Annie Jump Cannon, 1924. Despite our differences, people from all walks of life— rural and urban—have always shared the same sky. But for the first time in human history, there are people in the world who have never seen the stars.